A systematic review of diagnostic and interventional techniques in non-occlusive hepatic artery hypoperfusion syndrome - Torkian, Pooya; Moghadam, Arash Dooghaie; Zimmerman, Joel; Kollitz, Megan; Teufel, Andreas; Ebert, Matthias; Rosenberg, Michael S.; Young, Shamar J.; Flanagan, Siobhan; Talaie, Reza (Abdominal radiology, 2024)
Objective This systematic review aims to elucidate the diagnostic capabilities of imaging techniques in identifying Non-Occlusive Hepatic Artery Hypoperfusion Syndrome (NOHAH) and to evaluate the efficacy and outcomes of splenic artery embolization (SAE), including the choice and placement of embolic agents. Materials and methods A comprehensive literature search was conducted using PubMed, CINAHL, and Scopus databases, adhering to PRISMA guidelines. Fifteen studies encompassing 240 patients treated with embolization (using coils or Amplatzer Vascular Plugs (AVP)) were analyzed. Key metrics assessed included patient demographics, embolization techniques, embolic agents, technical success, radiologic findings pre- and post-embolization, and complication rates. Results Among the 240 patients studied, 177 (73.8%) were reported by gender, with a majority being male (127/177, 71.7%). Doppler ultrasonography (DUS) emerged as the primary initial screening tool in 80% of studies. The hepatic arterial resistive index (RI) was a critical parameter, with mean values significantly decreasing from 0.84 pre-embolization to 0.70 post-embolization (p < 0.001). All cases confirmed technical success via digital subtraction angiography, revealing delayed hepatic arterial filling without stenosis or thrombosis. Coils were the predominant embolic agent, used in 80.8% of patients, followed by AVP in 16.3%. The overall mortality rate was 4.58%, with 29 major and 3 minor complications noted. Notably, proximal placement of coils in the splenic artery was associated with lower mortality rates compared to distal placement and showed comparable complication rates to AVPs. Conclusion DUS is a reliable screening modality for NOHAH, with post-SAE assessments showing significant improvements. The choice and location of embolization significantly impact patient outcomes, with proximal placement of coils emerging as a preferable strategy due to lower mortality rates and comparable complication profiles to alternative methods.